Evaluation of patients with positive anti-mitochondrial antibody in laboratory conditions - Serdar Olt; İhsan Uslan and Ahmet Tarık Eminler and İhsan Hakkı Çiftçi and Ali Tamer (Turkish Journal of Gastroenterology, 2019)
-